2005
DOI: 10.1021/tx049703a
|View full text |Cite
|
Sign up to set email alerts
|

Quinone Methide Formations in the Cu2+-Induced Oxidation of a Diterpenone Catechol and Concurrent Damage on DNA

Abstract: Terpene quinone methides have been isolated from natural resources and exhibit broad biological activities against bacteria, fungi, and tumor cells through the reactive quinone methide (QM) moiety. The biological potential of the oxidation of terpene QM precursors, however, has not been assessed even though Cu(2+)-induced oxidation of catechol shows detrimental effects on cells. In this study, a diterpenone catechol was investigated as a precursor of terpene QM under aqueous conditions in the presence of Cu2+.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…In these systems, DNA damage is caused by ROS generated by reducing Cu 2+ to Cu + or by direct reduction of O 2 to various ROS, including CuOOH, 1 O 2 , H 2 O 2 , and OH. 62,[270][271][272][273][274] Wang et al 62 treated viral DNA with Cu 2+ (10 mM) and epigallocatechin gallate (EGCG, 1-50 mM) and observed DNA cleavage in a dose dependent manner with respect to EGCG concentration. The authors proposed 1 O 2 formation from reaction of Cu + and H 2 O 2 , likely through the formation of a CuOOH species.…”
Section: Copper and Zincmentioning
confidence: 99%
“…In these systems, DNA damage is caused by ROS generated by reducing Cu 2+ to Cu + or by direct reduction of O 2 to various ROS, including CuOOH, 1 O 2 , H 2 O 2 , and OH. 62,[270][271][272][273][274] Wang et al 62 treated viral DNA with Cu 2+ (10 mM) and epigallocatechin gallate (EGCG, 1-50 mM) and observed DNA cleavage in a dose dependent manner with respect to EGCG concentration. The authors proposed 1 O 2 formation from reaction of Cu + and H 2 O 2 , likely through the formation of a CuOOH species.…”
Section: Copper and Zincmentioning
confidence: 99%
“…Quinone methides (QMs) are reactive carbon electrophiles, frequently involved in chemical and biological processes, targeting amino acids, , proteins, , and nucleic acids, which are generated from stable and suitable precursors (QMPs), upon activation. Consequently, several strategies have been successfully developed for biocompatible generation of QMs, including tautomerization, oxidation, reduction, acid or base catalysis, and photolysis. Concerning recent biological applications, a mild QMs generation was exploited to achieve bioorthogonal ligations, which is very useful in the labeling of biomolecules in living systems. , Photogeneration of QMs has been a thoroughly investigated area, as (i) it can be performed under very mild conditions in the absence of activating reactants and (ii) the QMs can be spectroscopically detected and kinetically characterized by transient absorption techniques such as laser flash photolysis (LFP). According to current literature, QM-photogeneration occurs from the lowest singlet excited state (S 1 ) of the QMP, by excited-state proton transfer (ESPT) to the solvent or excited state intramolecular proton transfer (ESIPT). The generation of QMs by ESIPT from Mannich bases is a pH-dependent process, being very efficient under aqueous solution when the QMPs are in their dipolar form .…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratories and others have applied the reversibility of quinone methide (QM) generation for efficient cross-linking and target-promoted alkylation of DNA. Related QMs had previously been implicated in biological activation of 2,6-di- tert -butyl-4-methylphenol, tamoxifen, and a variety of natural products including mitomycin and certain diterpenone catechols . Initial model studies suggested a selectivity of QM for weak nucleophiles and an ability of some adducts to form reversibly. , Further investigation revealed that this unusual selectivity was a function of QM adduct stability rather than initial product formation. In contrast to earlier assumptions, the strongest nucleophiles of DNA reacted most quickly with a simple o -QM model to form kinetic products.…”
Section: Introductionmentioning
confidence: 99%